Joe Biden's Efforts to Restore and Expand the Scope of DACA in the United States During the 2020–2024 Period - Ardelia, Putri; Hikmawan, Rizky (Insignia: Journal of International Relations, 2025)
Abstract Immigration is a multifaceted issue that significantly impacts various areas. In a lot of developed countries, such as the U.S., this causes a new problem, which is illegal immigration. As an effort to eliminate this issue, the U.S. has implemented the DREAM Act in 2001, followed by DACA in 2012, which was created by Obama, that aims to protect illegal immigrants who came to the U.S. as children. However, DACA faced significant challenges when Trump became president and attempted to repeal DACA and successfully made changes to the policy. Biden, as Trump’s successor, adopted a different approach to the issue of illegal immigration, seeking to restore and expand the scope of DACA. With this in mind, this study aims to analyze and evaluate Biden's efforts to restore and expand DACA during the 2020–2024 period, using Lee & Anderson's immigration policy framework, particularly regarding the policy process. John Rourke's five idiosyncratic indicators to assess the obstacles Biden faced in restoring and expanding DACA's scope. The research employs a descriptive qualitative method with secondary data and data analysis. The findings indicate that Biden's efforts. Such as the codification of DACA, the Build Back Better Bill, the U.S. Citizenship Act of 2021, and providing ACA access to Dreamers, were hindered by Congressional disagreement, court rulings, and Biden's idiosyncratic factors, such as personality, physical and mental health, ego, experience, and the reality not aligning with his agenda. Keywords: DACA, Joe Biden, illegal immigrants Abstrak Imigrasi merupakan isu yang kompleks dan berdampak signifikan pada berbagai bidang. Di banyak negara maju, seperti AS, hal ini menimbulkan isu baru, yaitu imigrasi ilegal. Sebagai upaya untuk mengatasi masalah tersebut, AS telah menerapkan DREAM Act pada tahun 2001, dilanjutkan oleh DACA pada tahun 2012 yang dibuat oleh Obama, yang bertujuan untuk memberikan perlindungan kepada imigran ilegal yang datang ke AS sebagai anak-anak. Namun, DACA menghadapi tantangan besar ketika Trump menjadi Presiden dan berusaha menghapus DACA serta berhasil membuat perubahan terhadap kebijakan tersebut. Biden, sebagai penerus Trump, mengadopsi pendekatan yang berbeda terhadap isu imigrasi ilegal, dengan berupaya untuk merestorasi dan memperluas cakupan DACA. Untuk itu, penelitian ini bertujuan untuk menganalisis dan mengevaluasi upaya Biden merestorasi dan memperluas DACA pada periode 2020–2024, dengan menggunakan konsep kebijakan imigrasi Lee & Anderson, terutama mengenai proses kebijakan, dan lima indikator idiosinkratik Rourke untuk mengevaluasi hambatan yang dihadapi Biden dalam merestorasi dan memperluas cakupan DACA. Metode yang digunakan yaitu kualitatif deskriptif dengan data sekunder, serta analisis data. Hasil penelitian menunjukkan bahwa upaya Biden, seperti kodifikasi DACA, RUU Build Back Better, U.S. Citizenship Act 2021, dan pemberian akses ACA kepada Dreamers, terhambat oleh ketidaksetujuan Kongres dan putusan pengadilan, serta faktor idiosinkratik dari Biden, seperti kepribadian, kondisi fisik dan mental, ego, pengalaman, dan realita yang tidak sesuai dengan agendanya. Kata kunci: DACA, Joe Biden, imigrasi ilegal